The effect of marriage on education of immigrants: evidence from a policy reform restricting spouse import - Helena Skyt Nielsen; Nina Smith; Aycan Celikaksoy (Institute for the Study of Labor (IZA), 2007)
We investigate the effect of immigrants' marriage behavior on dropout from education. To identify the causal effect, we exploit a recent Danish policy reform which generated exogenous variation in marriage behavior by a complete abolishment of spouse import for immigrants below 24 years of age. We find that the abrupt change of marriage behavior following the reform is associated with improved educational attainment of young immigrants. The causal impact of marriage on dropout for males is estimated to be around 20 percentage points, whereas the effect for females is small and mostly insignificant. We interpret the results as being consistent with a scenario where family investment motives drive the behavior of males, while the association between marriage and dropout for females is driven by selection effects. The estimated causal effect varies considerably across subgroups.
Keywords: 330; Migranten; Ehe; Bildungsverhalten; Männer; Frauen; Familiensoziologie; Dänemark